Raport o stanie dyskursu krytycznoliterackiego w Polsce - Gleń, Adrian (Er(r)go. Teoria - Literatura - Kultura, 2017)
Adrian Gleń Zakład Literatury Współczesnej i Teorii Literatury Uniwersytet Opolski A Report on the Condition of the Critical Discourse in Poland Abstract: The article is an attempt to describe the condition of the discourse of literary criticism as practiced in Poland. The author investigates the process of gradual impoverishment and despecification of the language of literary criticism, which reveals itself via diverse socio-literary phenomena, such as the demand for shortenings and evaluative character of literary criticism, the places where literary criticism appears, the disappearance of the quality of the dialogue, and the way literary criticism functions in the Polish contemporary publishing market. A separate part of these considerations is devoted to the overview of the critics’ approaches to the condition of the discourse of literary criticism and the discussion of the postulate of the “privatization” of literary criticism. Keywords: literary criticism, Poland, critical discourse, scholarly publishing, academic dialog Raport o stanie dyskursu krytycznoliterackiego w Polsce Tekst stanowi próbę opisu stanu dyskursu krytycznoliterackiego w Polsce. Autor śledzi proces stopniowej pauperyzacji i despecyfikacji języka krytyki literackiej, ujmując owe zjawiska przez pryzmat zjawisk socjoliterackich (określone zapotrzebowanie na skrótowość i ewaluacyjny charakter krytycznoliterackiego pisania, miejsca ujawniania dyskursu krytycznoliterackiego, zanik dialogowości w tymże dyskursie, funkcjonowanie krytyki literackiej na współczesnym rynku wydawniczym w Polsce). Osobną część rozważań stanowi przegląd stanowisk krytyków wobec kondycji dyskursu krytycznoliterackiego oraz dyskusja na temat postulowanej tzw. „prywatyzacji pisania” krytycznoliterackiego. Słowa kluczowe: krytyka literacka, Polska, dyskurs krytyczny, wydawnictwa akademickie, dialog akademicki